Newsroom Management of Badminton News Media in Indonesia - Narayana Mahendra Prastya; Farahdilla Puspa; Regita Ramadhani; Ida Nuraini Dewi Kodrat Ningsih (School of Journalism, Faculty of Communication Sciences, Universitas Padjadjaran, 2022)
The Indonesian National Badminton team is one of the most successful national teams in international competition. Such success has brought a significant contribution to Indonesian national pride. However, in terms of popularity, this sport is less popular when compared to football. Consequently, there are only a few Indonesian sports media that specializes in reporting and discussing badminton. This study aims to determine the newsroom management of badminton media in Indonesia, in particular Majalah Bulutangkis and bulutangkis.com. Newsroom management is an important element in mass media. This study uses the qualitative method, with interviews as data collecting techniques. The informants are editors-in-chief from bulutangkis.com and Majalah Bulutangkis. In general, the results of the study show that both media regularly cover badminton tournaments participated by Indonesian badminton players. News related to events outside the field is also presented, including the side story related to badminton to keep the readers from being bored. From an organizational perspective, both media are experiencing a lack quantity of journalists, so they use freelance contributors or recruit volunteers. In practice, both media use websites as a platform to provide information and the Readers Forum to build interaction with their readers as well as invite readers to submit articles. This condition causes both media to be less active in maintaining their social media accounts. The evaluation stage is carried out by looking at the accuracy of the information and the use of language.